The Influence Of Brand Image, Taste, And Price Perception On Purchasing Decisions For Sarimi Instant Noodles In Surabaya - Permata ELG Purba; Hery Pudjoprastyono (UNIVED Press, 2024)
Sarimi is a brand of instant noodles in Indonesia produced by Indofood CBP Sukses Makmur which was launched in 1982. Just like other instant noodle products, sarimi is sold in various types of products and flavors according to consumer needs. With so many brands of instant noodles in Indonesia, the reality is that sales of Sarimi instant noodles have decreased from year to year. This research aims to determine the influence of brand image, taste and price perception on purchasing decisions for sarimi instant noodles. The population of this study were Active Students of UPN